2020
DOI: 10.1155/2020/7905750
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Solution for Predicting Buried Pipeline Response Induced by Tunneling Based on a Uniform Ground Movement Model

Abstract: The construction of shield tunnels inevitably causes displacement of the surrounding soil and additional stress and deformation of the buried pipeline. An energy solution for predicting the deformation of buried pipelines caused by tunneling is proposed in this study. First, based on the uniform ground movement model, the interval of the free displacement field of soil around the pipeline induced by tunneling is calculated. Then, we use the Pasternak model to establish the total potential energy equation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…As the capital city of Anhui Province in southeastern China, Hefei has multiple subway lines under simultaneous construction. e impact assessment of subway construction on the surrounding environment is particularly important [24]. ere are few studies on the PIP excavation in this area, and it is hoped that the results of this study will provide guidance for the follow-up subway construction.…”
Section: Introductionmentioning
confidence: 95%
“…As the capital city of Anhui Province in southeastern China, Hefei has multiple subway lines under simultaneous construction. e impact assessment of subway construction on the surrounding environment is particularly important [24]. ere are few studies on the PIP excavation in this area, and it is hoped that the results of this study will provide guidance for the follow-up subway construction.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, it is not rare to find an excavation that is adjacent to preexisting subway tunnels, piles, pipelines, or other shallowly buried facilities [1][2][3][4][5]. Inevitably, the adja-cent excavation has an adverse effect on the constructed structures or facilities, and many studies have focused on this issue in recent decades [6][7][8]. It has been found that the excavation-induced redistribution of ground stress can lead to the generation of additional stress and deformation in the tunnel structure.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the equivalent soil shear strain proposed by Marshall et al [11], Klar et al [12] solved the difficult problem of determining relative pipeline-soil displacement and offered the procedure for calculating the maximum bending moment of pipelines caused by tunneling by considering soil nonlinearity. Based on the Pasternak model and a uniform ground movement model, an energy solution for predicting buried pipeline response induced by tunneling was proposed by Shi et al [13]. Multiple research methods were applied by Zhang et al [14], who investigated the interaction mechanism between an existing pipeline and quasirectangular tunneling in clays.…”
Section: Introductionmentioning
confidence: 99%